2020
DOI: 10.1093/qjmed/hcaa325
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation product is a reliable indicator for identifying metabolic syndrome: the China Multi-Ethnic Cohort (CMEC) Study

Abstract: Background Previous studies have shown that lipid accumulation product (LAP) was associated with the risk of cardiometabolic disease. It is not clear whether LAP could be used as a marker to identify metabolic syndrome (MetS) among Chinese ethnic groups. Aim: To assess the reliability of LAP as a maker to identify MetS among Dong adults. Design: Population-based cross-sectional study. Method We included 6494 Dong individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In 2006, the lipid accumulation product (LAP) 12 was introduced, which incorporated triglycerides (TG) and WC and was adjusted by gender, which was thought to offer a better evaluation of visceral adipose tissue and had a stronger association with metabolic status. Some studies 13 , 14 reported that LAP was an efficient marker of MS in general adult populations. In 2015, the cardiometabolic index (CMI) 15 was proposed as a new index to evaluate visceral obesity by using blood lipid parameters and WHtR.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, the lipid accumulation product (LAP) 12 was introduced, which incorporated triglycerides (TG) and WC and was adjusted by gender, which was thought to offer a better evaluation of visceral adipose tissue and had a stronger association with metabolic status. Some studies 13 , 14 reported that LAP was an efficient marker of MS in general adult populations. In 2015, the cardiometabolic index (CMI) 15 was proposed as a new index to evaluate visceral obesity by using blood lipid parameters and WHtR.…”
Section: Introductionmentioning
confidence: 99%
“…study from CMEC that lipid accumulation product could be a reliable index for identifying MetS. (15). Besides, a 5-year followup indicated that adults with a low HDL level were more likely to develop MetS in the long run (16).…”
Section: Discussionmentioning
confidence: 99%
“…The sociodemographic characteristics, health‐related behaviours and medical history, including sex, age, marital status, residency, educational level, smoking status, alcohol drinking, tea intake, beverage intake, physical activity, taking antiarrhythmic or antihypertensive drugs, family history of hypertension or diabetes, coronary heart disease, stroke and abnormal thyroid function were collected by face‐to‐face interviews. Details about the investigation were previously published 21,22 …”
Section: Methodsmentioning
confidence: 99%
“…Details about the investigation were previously published. 21,22 Smokers were defined as people who had smoked 100 or more cigarettes during their lifetime. 23 Alcohol drinkers were defined as having consumed alcohol once or more times per week in the past half year.…”
Section: Data Collection and Measurementsmentioning
confidence: 99%